2007
DOI: 10.1097/rli.0b013e31804ffd49
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Detection by Diffusion-Weighted MRI and ADC-Mapping???Initial Clinical Experiences in Comparison to PET-CT

Abstract: DWI is a feasible clinical technique, improving the assessment of metastatic spread in routine magnetic resonance imaging examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 23 publications
1
43
0
4
Order By: Relevance
“…The lower ADC values were obtained in prostate carcinoma, hepatocellular carcinoma, colorectal carcinoma, melanoma, neuroblastoma, and breast carcinoma when compared to benign lesions of each organ (25)(26)(27)(28)(29). As in most of the malignancies of other organs studied, we found markedly lower ADC values in malignant thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The lower ADC values were obtained in prostate carcinoma, hepatocellular carcinoma, colorectal carcinoma, melanoma, neuroblastoma, and breast carcinoma when compared to benign lesions of each organ (25)(26)(27)(28)(29). As in most of the malignancies of other organs studied, we found markedly lower ADC values in malignant thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The Jeong simplification of WHO classification includes low-risk thymomas, high-risk thymomas, and thymic carcinomas [9]. The Masaoka-Koga system includes early (stage I-II) and advanced thymomas (stage III-IV) [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 DWI has been used to detect malignancies in the body because it has been shown that the diŠusion of water molecules in malignant tumors is slower than that of the normal parenchyma. [3][4][5][6] The breast is a popular target for DWI, and many reports demonstrate its clinical utility for breast tumors. [7][8][9][10][11][12][13][14][15][16][17][18][19] In a meta-analysis of DWI of breast tumors performed with 1.5-tesla MR imaging, Tsushima and associates 19 reported sensitivity of 0.89 and speciˆcity of 0.77, comparable to results of meta-analysis of contrastenhanced breast MR imaging.…”
Section: Introductionmentioning
confidence: 99%